(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The question raised in the introduction of the article was as follows: “What is the role and significance of the data on quality-related costs for a company’s information system. The author attempted to prove the significance and necessity of distinguishing the quality-related costs. The author highlighted the importance of data on quality-related costs in the decision-making process. The following models were discussed and graphically-presented: the company’s quality-related cost account as well as quality-related costs in the company’s cost management. The conclusive part of the article provides a final answer to the question on the importance of the quality-related costs in the company’s information system.